Menguatkan Ekosistem Pendidikan Melalui Kontribusi Manajemen Pendidikan Islam dalam Pengembangan Keterampilan Abad ke-21 - Nadilla Aleyda Maqhfira Agustin; Sembodo Ardi Widodo; Dewimah Putri Tazkiyah; Ahmad Syawal (CV. ITTC INDONESIA, 2025)
Islamic Education Management (MPI) holds immense potential for cultivating a generation that is intellectually astute, morally upright, and equipped with 21st-century skills, thereby making a positive contribution to society and the nation. SMK Al-Achyar exemplifies this by integrating Islamic spiritual and ethical values with global competency demands, proving to be highly essential. Concrete programs ensure students are well-prepared to navigate the complexities of the information age. Furthermore, this success is bolstered by strategic partnerships with businesses, industries, and the community, which provide valuable opportunities for students. This research employed a qualitative approach with a descriptive method, integrating in-depth interviews as the primary data collection technique. Data analysis was conducted inductively using the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing, ensuring comprehensive and verified findings. The study results indicate that programs like Kitab Kuning, public speaking, and digital literacy effectively prepare students for challenges. This success is consistently driven by the strategic utilization of information technology as an accelerator in the learning process.